1998
DOI: 10.1007/s003810050223
|View full text |Cite
|
Sign up to set email alerts
|

Multiple shunt failures: an analysis of relevant factors

Abstract: Ventricular shunts that require multiple revisions are familiar to pediatric neurosurgeons. We conducted a retrospective study to determine whether patients who require repeated shunt revisions represent a particular cohort within shunted hydrocephalic children. The clinical records of 244 children who had undergone shunt procedures between January 1990 and January 1996 were examined. They were divided into group 1: children with no shunt failure (n=136), group 2: children with one shunt revision (n=52), group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
72
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 14 publications
7
72
2
1
Order By: Relevance
“…One third of all shunt failures are thought to be due to malfunction of the distal cathether which may be caused by dislocation or obstruction or migration into the anterior abdominal wall 8,20) . The distal failure rate may be higher in patients with abdominal adhesions, obesity, or scoliosis 17) .…”
Section: Discussionmentioning
confidence: 99%
“…One third of all shunt failures are thought to be due to malfunction of the distal cathether which may be caused by dislocation or obstruction or migration into the anterior abdominal wall 8,20) . The distal failure rate may be higher in patients with abdominal adhesions, obesity, or scoliosis 17) .…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, prior research has identified several variables that appear to influence shunt survival, including a patient's age, number of prior revisions, and etiology of hydrocephalus; 5,6,10,19,21,25,34 however, the literature includes conflicting results on this topic, and several studies may indicate that shunt survival is impacted by one or more of these variables, while others do not. 4,6,10,19,21,25,34 Our study, unfortunately, has added to this confusing picture.…”
Section: Discussion Our Findingsmentioning
confidence: 99%
“…23 The identification of putative predictors of shunt survival has been an area of active research. 5,6,10,19,21,25,29,34 In the study by Berry et al, risk factors for shunt revision (initial and multiple) were young age, hospitals with lower shunt surgery volume, and type of hydrocephalus (e.g., obstructive and spina bifida). 4 Tuli et al found that age, time interval since last revision, and underlying diagnosis were predictors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Many studies have sought to identify risk factors for shunt failure. 5,10,13,15,27,29,37,48 To date, there is no consensus within the literature on any clinical, demographic, or procedural variable as being predictive of shunt failure. We recently conducted our own institutional review of 739 shunt operations performed over a 4-year period and found no predictive risk factors for shunt failure within 90 and 180 days of surgery (de novo or revision).…”
mentioning
confidence: 99%